Assessment of Patterns of Dorsal Venous Plexus and Veins of the Upper Limb - Hiware, Sanket Dadarao; Hafiz Daimi, Syed Rehan; Shaikh, Siraj Ahmed Hasham; Khwaja, Moizuddin Jawaduddin; Badaam, Asim Mohsin; Siddiqui, Faiza Banu; Bokariya, Pradeep; Sharma, Nidhi (Journal of evolution of medical and dental sciences, 2020)
BACKGROUND Superficial and deep group of veins form the upper limb veins. In this study, we evaluated patterns in the dorsal venous plexus and veins of upper limbs. METHODS This prospective observational study conducted from October 2019 to May 2020 comprised of 52 adults with age ranging from 18 - 60 years of both genders were recruited in the study. The materials used in the study was thread, rubber, pen or pencil (marker in some cases), tourniquet, measuring tape and camera. The researchers tied a tourniquet in an oblique fashion after making the arm abducted superolaterally up to greater tubercle of humerus and inferomedially extending up to the level of lower border of teres major. The subjects were instructed to continuously flex and extend the forearm for 2 - 3 times and this helped in making the superficial veins of upper limb more prominent. Site of origin, variations, course and length of vein were recorded. The length of the cephalic vein and basilic vein was noted. Dorsal venous network pattern was studied. RESULTS The mean length of left cephalic vein was 53.2 [+ or -] 5.1 cm and right was 53.1 [+ or -] 4.9 cm, left basilic vein was 50.6 [+ or -] 4.8 cm and right was 50.2 [+ or -] 4.3 cm, left median cubital vein was 11.8 [+ or -] 4.2 cm and right was 11.2 [+ or -] 3.7 cm and left median vein of forearm was 18.4 [+ or -] 1.7 cm and right was 18.1 [+ or -] 1.9 cm. Within left and right veins, a nonsignificant difference was observed (p > 0.05). the most common pattern of venous plexus was type I seen in 14 on left side and 16 on right side and type II seen on 10 on left side and 12 on right side. CONCLUSIONS There were eleven different pattern of dorsal venous plexus in study population. KEY WORDS Cubital, Dorsal Venous Plexus, Veins